1958
DOI: 10.2307/138618
|View full text |Cite
|
Sign up to set email alerts
|

Some Obstacles to Democracy in Quebec

Abstract: Historically, French Canadians have not really believed in democracy for themselves; and English Canadians have not really wanted it for others. Such are the foundations upon which our two ethnic groups have absurdly pretended to be building democratic forms of government. No wonder the ensuing structure has turned out to be rather flimsy.The purpose of the present essay is to re-examine some of the unstated premises from which much of our political thinking and behaviour is derived, and to suggest that there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1967
1967
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…L'origine de cette hypothèse remonte à la Conquête et à la formation du Bas-Canada alors que lord Durham écrit dans son rapport de 1839 suivant la rébellion des patriotes : « I expected to find a contest between a government and a people : I found two nations warring in the bosom of a single state : I found a struggle not of principles, but of race 11 . » Cette hypothèse est également partagée par d'autres auteurs, tels que Pierre Elliott Trudeau 12 , Jean-Pierre Wallot 13 , Murray Greenwood 14 et Renaud Séguin 15 . En effet, Trudeau affirme que les Canadiens français n'ont jamais voulu de la démocratie, mais qu'une fois celle-ci imposée par les autorités britanniques, ils se sont servis des institutions démocratiques pour assurer leur survie.…”
Section: Les Partis Politiques Au Bas-canadaunclassified
“…L'origine de cette hypothèse remonte à la Conquête et à la formation du Bas-Canada alors que lord Durham écrit dans son rapport de 1839 suivant la rébellion des patriotes : « I expected to find a contest between a government and a people : I found two nations warring in the bosom of a single state : I found a struggle not of principles, but of race 11 . » Cette hypothèse est également partagée par d'autres auteurs, tels que Pierre Elliott Trudeau 12 , Jean-Pierre Wallot 13 , Murray Greenwood 14 et Renaud Séguin 15 . En effet, Trudeau affirme que les Canadiens français n'ont jamais voulu de la démocratie, mais qu'une fois celle-ci imposée par les autorités britanniques, ils se sont servis des institutions démocratiques pour assurer leur survie.…”
Section: Les Partis Politiques Au Bas-canadaunclassified
“…This phenomenon is equally unsurprising in the Canadian context. The primary mover behind the Canadian Charter of Rights , Pierre Trudeau (himself a Catholic), has noted in a number of his scholarly works, for example, that among the staunchest foes in the 1950s of the modernization and secularization of Quebec, the centre of Canadian Catholicism, was the Catholic Church (see, for example, Trudeau 1958, 302). Until the province's “Quiet Revolution” of the 1960s, the Church was extremely influential in then-Premier Maurice Duplessis's socially conservative government, an influence that included virtually direct control over the province's schools as well as ongoing encouragement of the premier in his government's efforts to suppress religious freedom for non-Catholics in the province (Botting 1993, 105–116).…”
Section: Catholic Political Leaders and Public Values: Same-sex Marrimentioning
confidence: 99%
“…Scholars from Tocquville's time to the mid-1970s have observed that, among European countries and their overseas offspring, Protestant countries have been more likely to give rise to democratic regimes that Catholic ones (Bollen, 1979;Huntington, 1991). Treadeau (1960) writing as a political scientist in the late 1950s, noted that Catholics have been closely linked to the state, adhering to a church which has been hierarchical, and authoritarian in spiritual matters. Lipset (1994) argues that Protestants, particularly the non-state-related sects, are less authoritarian, more congregational, participatory and individualistic.…”
Section: Confession Reformation and Accountabilitymentioning
confidence: 99%